PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS KETAHANAN PANGAN PROVINSI SULAWESI TENGGARA - Ida Bagus Agung Surya A; Eliyanti Agus Mokodompit; Adnan Hakim; Asrip Putera; Yusuf Yusuf (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to examine and analyze the effect of work motivation and work discipline on employee performance. This study uses a sampling technique, namely a saturated sample of 60 samples consisting of secretaries, heads of divisions, heads of sections, and functional staff of the Food Security Service of Southeast Sulawesi Province. Methods of data collection using a questionnaire. The data analysis method uses multiple linear regression analysis with the help of the IBM SPSS Statistics Version 26 software application.The results of this study indicate that (1) work motivation partially has a positive effect on employee performance. (2) Work Discipline partially has a positive effect on employee performance. (3) Motivation and Work Discipline simultaneously have a positive effect on employee performance. The conclusion of this study is that the higher the work motivation, the higher the performance of the resulting employee as well as the higher the work discipline, the higher the employee's performance, and work motivation and work discipline have an interaction with employee performance.